Developing an archaeological archives framework for the Palawan island palaeohistory research project - Aldiano, Leizel M. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Archaeological archives include all materials arising from archaeological activities and their documentation. The archaeological sites and deposits in Palawan hold the material remains of an enormous complex of cultural and historical evidence that provide tangible evidence of the past. The study sought to investigate the state of archaeological archiving or any resembling practices of the Palawan Island Paleohistory Research Project (PIPRP), & to consequently develop an archaeological archives framework for it. The study used a qualitative-descriptive research design to describe the archival status of the archaeological records of the PIPRP. Participant observation in actual field excavations and developmental interviews of key stakeholders were conducted to gather information about the creation, reception, analysis, storage, and access of the PIPRP records. Gathered information were used to appropriate selected international best practices on archeological archiving as to develop a framework for the PIPRP archaeological archives.